2020
DOI: 10.1007/s10853-020-05264-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and hardness during artificial aging of an ultrafine-grained Al-Zn-Mg-Zr alloy processed by high pressure torsion

Abstract: An ultrafine-grained (UFG) Al-4.8%Zn-1.2%Mg-0.14%Zr (wt%) alloy was processed by high pressure torsion (HPT) technique and then aged at 120 and 170 °C for 2 h. The changes in the microstructure due to this artificial aging were studied by X-ray diffraction and transmission electron microscopy. It was found that the HPT-processed alloy has a small grain size of about 200 nm and a high dislocation density of about 8 × 1014 m−2. The majority of precipitates after HPT are Guinier–Preston (GP) zones with a size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…annealing the HPT-processed sample for 2 h at 120°C, the average grain size was practically unchanged, and it increased only to about 300 nm at 170°C, showing a stable UFG structure in this sample [14]. An unusually high strain rate sensitivity, m, of 0.43 ± 0.02 was obtained by using nanoindentation creep test in the same temperature region, indicating that superplasticity can be expected at low temperatures.…”
Section: Resultsmentioning
confidence: 76%
“…annealing the HPT-processed sample for 2 h at 120°C, the average grain size was practically unchanged, and it increased only to about 300 nm at 170°C, showing a stable UFG structure in this sample [14]. An unusually high strain rate sensitivity, m, of 0.43 ± 0.02 was obtained by using nanoindentation creep test in the same temperature region, indicating that superplasticity can be expected at low temperatures.…”
Section: Resultsmentioning
confidence: 76%
“…In the meantime, the recent works have shown that the formation of UFG states in Al alloys with a regulated distribution of alloying elements to form secondary hardening phases as well as segregations or interlayers along grain boundaries can lead to a unique combination of properties, when the strength, plasticity and electrical conductivity of the material simultaneously increase [ 20 , 21 , 22 ]. In addition, it was shown that grain refinement to the nanoscale range allows for realizing the SP effect at low and even ultralow (below 0.5 T m ) temperatures [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Under such conditions, the thermally induced degradation of the UFG microstructure could be prevented, which would ensure maintaining high strength of Al alloys after SP forming.…”
Section: Introductionmentioning
confidence: 99%
“…Gubicza et al [14] processed the ultrafine-grained (UFG) Al-4.8%Zn-1.2%Mg-0.14%Zr alloy by high-pressure torsion (HPT) technique and then aged at 120 and 170 °C for 2 hours. These microstructural changes due to artificial aging were studied by X-ray diffraction and transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%